Trends in bioconversion of lignocellulose: biofuels, platform chemicals & biorefinery concept - Menon, Vishnu; Rao, Mala (Progress in Energy and Combustion Science, 2012)
Bioconversion of renewable lignocellulosic biomass to biofuel and value added products are globally gaining significant prominence. Market forces demonstrate a drive towards products benign to natural environment increasing the importance of renewable materials. The development of second generation bioethanol from lignocellulosic biomass serves many advantages from both energy and environmental point of views. Biomass an inexpensive feedstock considered sustainable and renewable, is an option with the potential to replace a wide diversity of fossil based products within the energy sector; heat, power, fuels, materials and chemicals. Lignocellulose is a major structural component of woody and non-woody plants and consists of cellulose, hemicellulose and lignin. The effective utilization of all the three components would play a significant role in the economic viability of cellulosic ethanol. Biomass conversion process involves five major steps, choice of suitable biomass, effective pretreatment, production of saccharolytic enzymes-cellulases and hemicellulases, fermentation of hexoses and pentoses and downstream processing. Within the context of production of fuels from biomass, pretreatment has come to denote processes by which cellulosic biomass is made amenable to the action of hydrolytic enzymes. The limited effectiveness of current enzymatic process on lignocellulose is thought to be due to the relative difficulties in pretreating the feedstocks. The present review is a comprehensive state of the art describing the advancement in recent pretreaments, metabolic engineering approaches with special emphasis on the latest developments in consolidated biomass processing, current global scenario of bioethanol pilot plants and biorefinery concept for the production of biofuels and bioproducts. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Consolidated biomass processing; Lifecycle assessment; Lignocellulose; Pre-treatment; Saccharifying enzymes; Value-added products

New insight into sugarcane industry waste utilization (press mud) for cleaner biobutanol production by using c. acetobutylicum nrrl b-527 - Nimbalkar, Pranhita R.; Khedkar, Manisha A.; Gaikwad, S. G.; Chavan, Pramod V.; Bankar, Sandip B. (Applied Biochemistry and Biotechnology, 2017)
In the present study, press mud, a sugar industry waste, was explored for biobutanol production to strengthen agricultural economy. The fermentative production of biobutanol was investigated via series of steps, viz. characterization, drying, acid hydrolysis, detoxification, and fermentation. Press mud contains an adequate amount of cellulose (22.3%) and hemicellulose (21.67%) on dry basis, and hence, it can be utilized for further acetone-butanol-ethanol (ABE) production. Drying experiments were conducted in the temperature range of 60–120 °C to circumvent microbial spoilage and enhance storability of press mud. Furthermore, acidic pretreatment variables, viz. sulfuric acid concentration, solid to liquid ratio, and time, were optimized using response surface methodology. The corresponding values were found to be 1.5% (v/v), 1:5 g/mL, and 15 min, respectively. In addition, detoxification studies were also conducted using activated charcoal, which removed almost 93–97% phenolics and around 98% furans, which are toxic to microorganisms during fermentation. Finally, the batch fermentation of detoxified press mud slurry (the sample dried at 100 °C and pretreated) using Clostridium acetobutylicum NRRL B-527 resulted in a higher butanol production of 4.43 g/L with a total ABE of 6.69 g/L. © 2017 Springer Science+Business Media New York Author keywords
Keywords: Acetone; Acetone butanol ethanols; Acidic pre treatments; Agriculture; Biobutanol; cellulose; Clostridium acetobutylicum; Detoxification; Drying; Drying Fermentation; FermentationSpoilage; Fermentative production; Pre-treatment; Press mud; Press mud Pretreatment; Response surface methodology; Sugar industry; Sulfur determination